'Fabrication of carboxylated conducting polymer/CNTs composites thin films for immunosensor application - P. Netsuwan (2018)
The analysis of two British cohort studies (of people born in 1958 or 1970) and one British panel study (of people born in the early 1980s) tracked the educational, employment and marital preferences of three generations of young people between ages 16 and 23/26. It found a steady decline in young people achieving their ambitions. Supporting evidence from in-depth interviews with parents and their children suggested that the perceived need, ability and opportunity to disconnect from tradition and to engage in autonomous decision-making had become the main drivers of aspirations. Although this autonomy was greater for current than previous generations, it remained socially inequitable, with parents and their children accepting the widening gap that separates past and present transitions to adulthood. © 2013 Taylor and Francis, LLC.